2014
DOI: 10.1111/apa.12826
|View full text |Cite
|
Sign up to set email alerts
|

An instructional video enhanced bag-mask ventilation quality during simulated newborn resuscitation

Abstract: A self-instructional video significantly improved bag mask PPV performance in inexperienced providers but did not improve mask leak in a model of neonatal resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…It is an attractive instructional method, for it combines the advantages of observational learning and audiovisual support, it always shows a perfect demonstration, and it could be more cost-effective and less time-consuming than conventional teaching. Several studies found promising results for VBI, including improved practical skills and increased self-confidence [7][8][9][10]. However, the majority of these studies used an instructional video as part of a self-directed learning approach instead of an in-hospital course [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is an attractive instructional method, for it combines the advantages of observational learning and audiovisual support, it always shows a perfect demonstration, and it could be more cost-effective and less time-consuming than conventional teaching. Several studies found promising results for VBI, including improved practical skills and increased self-confidence [7][8][9][10]. However, the majority of these studies used an instructional video as part of a self-directed learning approach instead of an in-hospital course [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Basic neonatal resuscitation requires that providers recognize when to initiate and stop PPV and additionally have the skills needed to provide these procedures effectively. Although many educational videos have been developed and used to teach these skills, no research has compared the efficacy of using these videos alone with their use in combination with an in-person instructor [ 22 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that video instruction prior to standard mask ventilation in novice operators improves performance. Diendl et al demonstrated that a self-instructional video significantly improved BMV performance in inexperienced providers using a neonatal airway simulator [7]. While video instruction on proper mask techniques for both the standard and Tao face masks may be an effective way to improve initial performance, there is likely also a component of self adjustment that occurs during the second mask attempt that explains improved performance during the second mask trial.…”
Section: Discussionmentioning
confidence: 99%